2011
DOI: 10.3389/fendo.2011.00073
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroids reduce social isolation-induced behavioral deficits: a proposed link with neurosteroid-mediated upregulation of BDNF expression

Abstract: The pharmacological action of selective serotonin reuptake inhibitor antidepressants may include a normalization of the decreased brain levels of the brain-derived neurotrophic factor (BDNF) and of neurosteroids such as the progesterone metabolite allopregnanolone, which are decreased in patients with depression and posttraumatic stress disorders (PTSD). The allopregnanolone and BDNF level decrease in PTSD and depressed patients is associated with behavioral symptom severity. Antidepressant treatment upregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 155 publications
(257 reference statements)
4
62
0
4
Order By: Relevance
“…Therefore, we studied the level of Allo in post-TDS rats after the administration of YL-IPA08 to substantiate this hypothesis. Our results showed decreased Allo levels in the prefrontal cortex and serum in post-TDS rats, which is consistent with preclinical studies (Pinna et al, 2003(Pinna et al, , 2006aNin et al, 2011). We also found that the lowered Allo levels were reversed by YL-IPA08 treatment in post-TDS rats, and that these effects were antagonized by PK11195, further suggesting that the anti-PTSD effects of YL-IPA08 were mediated by binding to TSPO and the subsequent synthesis of Allo.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, we studied the level of Allo in post-TDS rats after the administration of YL-IPA08 to substantiate this hypothesis. Our results showed decreased Allo levels in the prefrontal cortex and serum in post-TDS rats, which is consistent with preclinical studies (Pinna et al, 2003(Pinna et al, , 2006aNin et al, 2011). We also found that the lowered Allo levels were reversed by YL-IPA08 treatment in post-TDS rats, and that these effects were antagonized by PK11195, further suggesting that the anti-PTSD effects of YL-IPA08 were mediated by binding to TSPO and the subsequent synthesis of Allo.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the socially isolated mouse fails to respond to the anxiolytic action of BZDs (diazepam and zolpidem) that fail to modulate GABAA receptors containing α4 and α6 subunits (Pinna et al, 2000(Pinna et al, , 2006bNin et al, 2011). Taken together, these data suggest that TSPO ligands that stimulate Allo biosynthesis might have an advantage over BZDs in the treatment of psychiatric disorders in which neurosteroid down-regulation and changes in GABAA receptor expression are operative (Pinna and Rasmusson, 2012).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, our results are concordant with other studies showing that the anxiolytic, and anti-depressant effects were elicited by allopregnanolone [11,12]. Allopregnanolone normalized the exaggerated contextual fear responses and anxiety of socially isolated mice [13].…”
Section: Discussionsupporting
confidence: 92%
“…For example, one such neurosteroid, 5α-pregnan-3α-ol-20-one (3α,5α-THP; a.k.a. allopregnanolone), is increased in rat brain following exposure to acute challenges/stressors, such as swim stress (Barbaccia et al, 1996; Purdy et al, 1991; Vallée et al, 2000), but decreased with chronic stressors, such as social isolation (Agís-Balboa et al, 2007; Bortolato et al, 2011; Dong et al, 2001; Matsumoto et al, 1999; Nin et al, 2011; Pibiri et al, 2008; Pinna and Rasmusson, 2012; Serra et al, 2004). These and other data suggest that neurosteroids, such as 3α,5α-THP, may have an important role for regulating the stress response.…”
Section: Introductionmentioning
confidence: 99%